Virologic and immunologic effectiveness at 48 weeks of darunavir-ritonavir- based regimens in treatment-experienced persons living with HIV-1 infection in clinical practice: A multicenter brazilian cohort - Biscione, Fernando Martín (2014)
Introduction: Published data addressing the effectiveness of darunavirritonavir (DRV/r)-based therapy for multiexperienced patients in developing countries are scarce. This study evaluated the 48-week virologic and immunologic effectiveness of salvage therapy based on DRV/r for the treatment of multidrug-experienced HIV-1-infected adults in Brazil. Materials and Methods: A multicenter retrospective cohort study was carried out with multidrug-experienced adults who were on a failing antiretroviral therapy and started a DRV/r-based salvage therapy between 2008 and 2010. The primary effectiveness end point was the proportion of patients with virologic success (plasma HIV-1 RNA <50 copies/mL at week 48). Results: At 48 weeks, 73% of the patients had HIV-RNA <50 copies/mL and a mean increase of 108 CD4 cells/mm3. Higher baseline viral load, lower baseline CD4 count, younger age, and 3 or more DRV/r-associated resistance mutations were significantly predictive of virologic failure. Concomitant use of raltegravir was strongly associated with virologic success. Conclusion: The use of DRV/r-based regimens for salvage therapy is an effective strategy in the clinical care setting of a developing country. © The Author(s) 2013.